Beispiel Nr: 01
$ \text{Gegeben:} ax^{2}+bx+c=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ ax^{2}+bx+c=0 \\ \textbf{Gegeben:} \\ 3x^2+3 =0 \\ \\ \textbf{Rechnung:} \\ \begin{array}{l|l|l|l} \begin{array}{l} \text{Umformen}\\ \hline 3x^2+3 =0 \qquad /-3 \\ 3x^2= -3 \qquad /:3 \\ x^2=\displaystyle\frac{-3}{3}\\ \text{keine Lösung} \end{array}& \begin{array}{l} \text{a-b-c Formel}\\ \hline 3x^{2}+0x+3 =0\\ x_{1/2}=\displaystyle\frac{-0 \pm\sqrt{0^{2}-4 \cdot 3 \cdot 3}}{2\cdot3}\\ x_{1/2}=\displaystyle \frac{-0 \pm\sqrt{-36}}{6}\\ \text{Diskriminante negativ keine Lösung} \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ 3x^{2}+0x+3 =0 \qquad /:3 \\ x^{2}+0x+1 =0 \\ x_{1/2}=\displaystyle -\frac{0}{2}\pm\sqrt{\left(\frac{0}{2}\right)^2-1} \\ x_{1/2}=\displaystyle 0\pm\sqrt{-1} \\ \text{Diskriminante negativ keine Lösung} \end{array}\\ \end{array}$